Characterizing two carbonate formations for CO₂-EOR and carbon geosequestration: applicability of existing rock physics models and implications for feasibility of a time lapse monitoring program in the Wellington Oil Field, Sumner County, Kansas. - Lueck, Anthony (Kansas State University, 2017)
This study focuses on characterizing subsurface rock formations of the Wellington Field, in Sumner County, Kansas, for both geosequestration of carbon dioxide (CO₂) in the saline Arbuckle formation, and enhanced oil recovery of a depleting Mississippian oil reservoir. Multi-scale data including rock core plug samples, laboratory ultrasonic P-&S-waves, X-ray diffraction, and well log data including sonic and dipole sonic, is integrated in an effort to evaluate existing rock physics models, with the objective of establishing a model that best represents our reservoir and/or saline aquifer rock formations. We estimated compressional and shear wave velocities of rock core plugs for a Mississippian reservoir and Arbuckle saline aquifer, based on first arrival times using a laboratory setup consisting of an Ult 100 Ultrasonic System, a 12-ton hydraulic jack, and a force gauge; the laboratory setup is located in the geophysics lab in Thompson Hall at Kansas State University. The dynamic elastic constants Young’s Modulus, Bulk Modulus, Shear (Rigidity) Modulus and Poisson’s Ratio have been calculated based on the estimated P- and S-wave velocity data. Ultrasonic velocities have been compared to velocities estimated based on sonic and dipole sonic log data from the Wellington 1-32 well. We were unable to create a transformation of compressional wave sonic velocities to shear wave sonic for all wells where compressional wave sonic is available, due to a lack of understandable patterns observed from a relatively limited dataset. Furthermore, saturated elastic moduli and velocities based on sonic and dipole sonic well logs, in addition to dry rock moduli acquired from core plug samples allowed for the testing of various rock physics models. These models predict effects of changing effective (brine + CO₂ +hydrocarbon) fluid composition on seismic properties, and were compared to known values to ensure accuracy, thus revealing implications for feasibility of seismic monitoring in the KGS 1-32 well vicinity.
Keywords: Rock physics; Carbon dioxide; Enhanced oil recovery; Fluid substitution; Geosequestration; Ultrasonic frequency